ANALISIS STRATEGI MARKETING MIX MODERN RITEL TERHADAP KEPUASAN MINAT MASYARAKAT DAN LOYALITAS MINAT MASYARAKAT - Hermawati, Adya (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Competition is not only enough business retaile by offering better quality products, competitive prices, creating a sense of satisfaction and provide better services to the public or the consumer, but the main addition to creating customer satisfaction, also try to build loyalty shopping public interest. The purpose of this study to determine the impact of modern retail marketing mix towards satisfaction of interest in public expenditure and its implications on the loyalty of the public interest in shopping. Using a purposive sampling of 150 respondents was obtained. The data analysis is a technique of multiple regression analysis and simple regression. The results were obtained through the direct influence of modern retail marketing mix becara simultaneously positive and significant effect on the public interest in shopping satisfaction, but factor prices partially not have a significant effect on the satisfaction of the public interest in shopping. Satisfaction of spending the public interest to have a positive influence and loyalty are very significant to the variable interest of public expenditure. This means that the satisfaction felt by the community for shopping will increase loyalty shopping. Key words: Marketing Mix, Satisfaction, Loyalty Shopping Community Interests